2017
DOI: 10.1007/s11064-017-2340-7
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Increases Synaptic Protein Levels via the MAPK/Erk Signaling Pathway and Nrf2/Trx Axis Following the Transplantation of Neural Stem Cells in a Rat Model of Traumatic Brain Injury

Abstract: Brain-derived neurotrophic factor (BDNF) plays an important role in promoting the growth, differentiation, survival and synaptic stability of neurons. Presently, the transplantation of neural stem cells (NSCs) is known to induce neural repair to some extent after injury or disease. In this study, to investigate whether NSCs genetically modified to encode the BDNF gene (BDNF/NSCs) would further enhance synaptogenesis, BDNF/NSCs or naive NSCs were directly engrafted into lesions in a rat model of traumatic brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…By binding to tropomyosin receptor kinase (Trk) receptors, BDNF and NGF activate the downstream signaling pathways such as phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) pathways and the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) [43, 44]. Several lines of evidence reported that Nrf2 activation can be regulated via PI3K/Akt and MAPK/ERK pathways and thereby affects redox homeostasis [17, 19, 4547]. Some studies suggested that BDNF can active antioxidant mechanisms constantly by inducing Nrf2 nuclear translocation [18].…”
Section: Discussionmentioning
confidence: 99%
“…By binding to tropomyosin receptor kinase (Trk) receptors, BDNF and NGF activate the downstream signaling pathways such as phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) pathways and the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) [43, 44]. Several lines of evidence reported that Nrf2 activation can be regulated via PI3K/Akt and MAPK/ERK pathways and thereby affects redox homeostasis [17, 19, 4547]. Some studies suggested that BDNF can active antioxidant mechanisms constantly by inducing Nrf2 nuclear translocation [18].…”
Section: Discussionmentioning
confidence: 99%
“…The blots were washed with TBST three times for 10 min each, incubated for 1 h with horseradish peroxidase-conjugated goat anti-rabbit or goat anti-mouse IgG (1 : 5000; ZSGB-Bio, China), and washed with TBST three times for 10 min each. The bound antibodies were detected by chemiluminescence using an ECL Western blotting detection system kit (GE Amersham Biosciences, Buckinghamshire, UK) and exposed to ChemiDOC™ XRS+ Image Lab™ Software (Bio-Rad Laboratories, Inc., Hercules, CA, USA) [46].…”
Section: Ros Staining and Fluorescence Microscopymentioning
confidence: 99%
“…Both the NF-B and MAPK immunomodulatory pathways strongly regulate the expression of diverse cytokines involved in immune responses, like microglial activation and recruitment [e.g., macrophage-colony-stimulating factor (M-CSF), MCP-1; Hommes et al, 2003;Cloutier et al, 2007;Liu et al, 2017]. These pathways also control the expression of neurotrophic and synaptotrophic factors and are involved in mechanisms of learning and memory (Sweatt, 2001;Kaltschmidt et al, 2006;Mattson and Meffert, 2006;Chen et al, 2017). Recent stud-ies have shown 40 Hz flicker changes protein phosphorylation patterns after weeks of exposure compared with no stimulation, but the immediate effect of flicker on protein phosphorylation in general and the immediate effects of flicker on these two key phosphoprotein pathways are still unknown (Adaikkan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%